1988
DOI: 10.1111/j.1939-0025.1988.tb01576.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutual aid for affective disorders: The manic depressive and depressive association.

Abstract: A study of 188 participants in the founding chapter of the National Depressive and Manic Depressive Association revealed characteristics of patient and family members, their satisfaction levels with various aspects of the association, and their perceptions of outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
0
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 6 publications
3
26
0
2
Order By: Relevance
“…Research showing this result exists in the areas of mental health (Galanter 1988;Kurtz 1988), addictions (Corrigan 1980;Polich et al 1980), and bereavement and parenting (Lieberman and Videca-Sherman 1986;Maton 1989), although these findings may be due in part to selfselection in group membership (Jacobs and Goodman 1989).…”
Section: Length Of I-group Participationmentioning
confidence: 68%
“…Research showing this result exists in the areas of mental health (Galanter 1988;Kurtz 1988), addictions (Corrigan 1980;Polich et al 1980), and bereavement and parenting (Lieberman and Videca-Sherman 1986;Maton 1989), although these findings may be due in part to selfselection in group membership (Jacobs and Goodman 1989).…”
Section: Length Of I-group Participationmentioning
confidence: 68%
“…Some studies have shown reduced level of psychiatric symptoms after mutual-help (Galanter, 1988) while others failed to find this difference (Kaufman, Schulberg, & Schooler, 1994;Raiff, 1982Raiff, , 1984. However, several studies showed a significant relationship between using mutual-help and decreased hospitalization (Galanter, 1988;Kennedy, 1989;Kurtz, 1988;Rappaport, 1993). Research also suggests that persons who are participating in mutual-help programs have larger support networks (Carpinello, Knight, & Janis, 1991;Rappaport et al, 1985) and enhanced self-esteem (Markowitz, DeMasi, & Carpinello, 1996).…”
mentioning
confidence: 92%
“…al., 2000;Davidson et. al., 1999;Klein, Cnaan, & Whitecraft, 1998;Kurtz, 1988;Powell et. al., 2001;Solomon & Draine, 1995 a,b).…”
Section: Introductionmentioning
confidence: 98%